Anomalous Segmental branch of pulmonary vein: V6 draining into the superior pulmonary vein - Sapkota, Sandeep; Thakur, Binay; Tiwari, Manoj; Khatiwada, Sagar; Bhattarai, Shachee; Kharel, Ashish; Adhikari, Mahesh Mani; Thapa, Shrijana (Nepalese Journal of Cancer, 2025)
Literatures have described different anatomical variations of pulmonary venous drainage. Even a single anatomical anomaly can eventually lead to surgical catastrophe, thus making the anticipation of these abnormalities crucial to perform a successful thoracic surgery procedure. We report a case of anomalous venous drainage of superior segment of the right lower lobe (V6) draining into the central venous branch of superior pulmonary vein. It wasn’t identified preoperatively but recognized intraoperatively and ensured after the meticulous dissection while doing Video assisted thoracoscopic right lower lobectomy (VATS) for lung cancer. Diagnostic Imaging and careful surgical dissection are of paramount importance to avoid intraoperative bleeding and inaccurate division of vein which may lead to venous gangrene of corresponding segment.